If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -10x = x + -10 Combine like terms: 2x + -10x = -8x -8x = x + -10 Reorder the terms: -8x = -10 + x Solving -8x = -10 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -8x + -1x = -10 + x + -1x Combine like terms: -8x + -1x = -9x -9x = -10 + x + -1x Combine like terms: x + -1x = 0 -9x = -10 + 0 -9x = -10 Divide each side by '-9'. x = 1.111111111 Simplifying x = 1.111111111
| 4x-8=7x-35 | | x^2+x-12=(x-a)(x-b) | | s/8=4.25 | | 5+2sinx-7=0 | | 9x^2-12x-41=0 | | V=AO | | (3x)/(e^(0.5X^2)) | | y=4E+07x | | -4y/-6 | | y=4E+07x-20026 | | a-(9b-13b)= | | 3+5n=35 | | -7x-10=59 | | 25t=30(t+10) | | 2j+18=32 | | 8z+4(5z+10)=0 | | 3y+9=2y-5 | | s/12=21/2 | | -7+40y=35y-6 | | n^2+1n-13=0 | | 17+13x=165 | | 2ln(x+2.8)=3.2 | | -4/5 | | 5-3x+7x=-39 | | 2(9s+4)-8=2(5s+3)-8 | | 4n-10n+35=1.2 | | 3x+x^2=48 | | 8/9g=1/3 | | 2x-8/=7 | | 2y^2+13y-45=0 | | -4r=21+3r | | 46+3x=5x-7 |